AN IoT BASED SMART HOME APPLIANCES SCHEDULING MANAGEMENT SYSTEM - Md Murshadul HOQUE; Mithun CHAKRABORTY; Joy RUDRA; Md Arif Iftekhar MAHMOOD (Carpathian Journal of Electrical Engineering, 2021)
This paper proposes a smart home appliance scheduling management (HASM) system based on demand response. An IoT based HASM system is developed to provide an efficient electricity consumption scheme to residential consumers for scheduling their appliances in a cost-effective way and smartly throughout a day. This smart load scheduler takes residential electricity users’ preferences to shift the appliances with deferrable characteristics at cost effective periods considering the user is aware of dynamic tariff information. The user interaction to the scheduling of loads provides maximum comfort level as well as saving of total electricity bill, and the effective utilization of demand response strategies to reduce peak hour electricity consumption. The results of this development indicate a reduction of daily energy consumption confirming the consumer comfort.